Aromatic disulfides as potential inhibitors against interaction between deaminase APOBEC3G and HIV infectivity factor - Yan Xiaoxuan; Chen Chao; Wang Chunxi; Lan Wenxian; Wang Jianguo; Cao Chunyang (Acta Biochimica et Biophysica Sinica)
APOBEC3G (A3G) is a member of cytosine deaminase family with a variety of innate immune functions. It displays activities against retrovirus and retrotransposon by inhibition of virus infectivity factor (Vif)-deficient HIV-1 replication. The interaction between A3G N-terminal domain and Vif directs the cellular Cullin 5 E3-ubiquitin ligase complex to ubiquitinate A3G, and leads to A3G proteasomal degradation, which is a potential target for anti-HIV drug. Currently, there are very few reports about stable small molecules targeting the interaction between A3G and Vif. In this study, we screened two series of small molecules containing carbamyl sulfamide bond or disulfide bond as bridges of two different aromatic rings. Five asymmetrical disulfides were successfully identified against interaction between A3G and Vif with the IC50 values close to or smaller than 1 μM, especially, not through covalently binding with A3G or Vif. They restore the A3G expression in the presence of Vif by inhibiting Vif-induced A3G ubiquitination and degradation. This study opens a way to the discovery of new anti-HIV drugs.